Effect Of Tax and Provision for Depreciation on Financial Performance of Selected Quoted Consumer Goods Firms in Nigeria: Array - Tayo Akinleye, Gideon; Olaoye, Clement Olatunji; Fajuyagbe, Samson Bamikole (The Journal of Accounting and Management, 2020)
Objective: The study analyzed the effect of tax and provision for depreciation on financial performance of selected quoted consumer goods firms in Nigeria, captured by reserve (2008-2017). Approach: The secondary data were sourced from the Published Annual Reports of selected quoted consumer goods firms in Nigeria, the study utilized panel least square analytical technique. Results: The result of the findings showed that tax (TAX), provision for depreciation (PFD) and profit before tax (PBT) positively influenced the financial performance of FLRM and NEST by 31811588 and 6310438 respectively. Also, it was discovered that tax (TAX), provision for depreciation (PFD) and profit before tax (PBT) in the period under consideration hindered the financial performance of DANG, UNIL and NEST by 18482966, 16389816 and 2461191 respectively in Nigeria. The Adjusted R-squared of 0.90, 0.17 and 0.23 for fixed, random and pooled effect model showed that 90, 17 and 23 percent variation in the financial performance of the quoted consumer goods firms in Nigeria can be explained by tax and profit before tax of the quoted consumer goods firms under consideration. Implications: The result implies that an increase in taxes and provision for depreciation of the quoted consumer goods firms in Nigeria brings about significant improvement in the financial performance. Therefore, since TAX, PFD and PBT enhanced the financial performance of the quoted consumer goods firms in Nigeria, they should adopt policies that will increase their profit level so as to enhance and improve better financial performance through increment in reserve. Value: We present the first test of the effect of tax and provision for depreciation on financial performance of quoted consumer goods firms in Nigeria